SHIFT IN UZBEKISTAN’S FOREIGN POLICY: ACTIVE ENGAGEMENT IN REPUTATION AND COOPERATION BUILDING VIA INTERNATIONAL ORGANIZATIONS (Scientific journal of the Fergana State University, 2023)
The foreign policy of Uzbekistan under President Shavkat Mirziyoyev has been characterized by innovative and liberal reforms. This article describes how country has taken on the role of an "initiative-taker," actively engaging in global-scale initiatives and multilateral diplomacy. Uzbekistan has organized conferences and adopted internationally-relevant resolutions, enhancing its international image and showcasing its goodwill. Uzbekistan actively advocates for peace, playing a linchpin role in the peace process in Afghanistan and promoting global non-proliferation regimes and regional security. In the international arena, the nation emphasizes the importance of tolerance, youth empowerment, and social support in combating terrorism and promoting global security. Uzbekistan also prioritizes regional cooperation among Central Asian states and takes pioneering actions to address environmental challenges, such as the Aral Sea desiccation. With its membership and active participation in various international organizations, and hosting of summits, Uzbekistan strengthens its position and image as an important subject of international politics.